Rancang Bangun System Informasi Pemesanan Custom-made Furniture Secara Online Menggunakan Algoritma Multiple Feedback Queue (MFQ) & Simple Additive Weighing (SAW) - Mohamad Chaerul Amin; Muhammad Rifqi (Universitas Mercu Buana, 2020)
Abstract - In this modern era, using technology in business has become common thing, moreover there’re a lot of business which using e-commers platform as their market. E-commers is where the seller can sell his goods by online without the buyer has to come to the store. This practice has made it easy for both party in doing business transactions, costumers just need to search what he needs on the platform without needed to look for the store which sell the product he wants. It is of course more effective and time effisient for both party by doing it online using the technology.The technology can also be used for furniture business, where we can order customize furniture for home furnishings. Using theFurniture application, costumers can get hand-made furniture as desire, we can choose which material tobe used, what color, and the dimension of the furniture. This application using MFQ (Multiple Feedback Queue) and SAW (Simple Additive Weighing) algorithm and for the method using RAD (Rapid Application Development). MFQ algorithm is used to determine the queue order which enter the system. The rules are if the order has more complex design, then the order will be put on hold and will be process after the easier design order is done. And this rules only applied for order which enter the system on the same date. The older date will using the same rules after the order on the younger date is finished. And to determine the sequence order SAW algoritm is used base on the time needed for the process as its variable.This application is expected tobe a bridge between the buyer and furniture entepneneur for easy search on the home furninshings. And also this application is for the buyer to custom-made the furniture without the need to seach the furniture entrepreneur who can do the customize. And for the furniture entrepreneur to advertise its product to the buyer for home furnishings.